Chinese Herbal Medicine for the Treatment of Children and Adolescents With Refractory Mycoplasma Pneumoniae Pneumonia: A Systematic Review and a Meta-Analysis - Ling, Xiaoying; Sun, Xun; Kong, Huimin; Peng, Shanshan; Yu, Zheng; Wen, Jiali; Yuan, Bin (Frontiers in Pharmacology, 2021)
Objectives: Chinese herb medicine (CHM) is one of the most popular complementary and alternative therapies, which has been widely used to treat Refractory Mycoplasma Pneumoniae Pneumonia (RMPP). However, the effect and safety of CHM remain controversial. Hence, we conducted this meta-analysis to evaluate whether CHM combination therapy could bring benefits to children and adolescents with RMPP. Methods: Seven databases were used for data searching through November 11, 2020 following the PRISMA checklist generally. Review Manager 5.3, TSA 0.9.5.10 Beta software and Stata16.0 were applied to perform data analyses. Mean difference (MD) or risk ratio (RR) was adopted to express the results, where a 95% confidence interval (CI) was applied. Results: In general, this research enrolled 17 trials with 1451 participants. The overall pooled results indicated that CHM was beneficial for children and adolescents with RMPP by improving the clinical efficacy rate [RR = 1.20, 95% CI (1.15, 1.25), P < 0.00001], shortening antipyretic time [MD = -2.60, 95% CI (-3.06, -2.13), P < 0.00001], cough disappearance time [MD = -2.77, 95% CI (-3.12, -2.42), P < 0.00001], lung rale disappearance time [MD = -2.65, 95% CI (-3.15, -2.15), P < 0.00001], lung X-ray infiltrates disappearance time [MD = -2.75, 95% CI (-3.33, -2.17), P < 0.00001], reducing TNF-α level [MD = -5.49, 95% CI (-7.21, -3.77), P < 0.00001]. Moreover, subgroup results suggested that removing heat-phlegm and toxicity therapy had more advantages in shortening antipyretic time, cough disappearance time, lung X-ray infiltrates disappearance time and reducing TNF-α level. Meanwhile promoting blood circulation therapy seemed to be better at relieving lung rale. However, regarding adverse events, the two groups displayed no statistical difference [RR = 0.97, 95% CI (0.60, 1.57), P = 0.91]. Conclusions: Despite of the apparently positive results in relieving clinical symptoms, physical signs and reducing inflammation, it is premature to confirm the efficacy of CHM in treating RMPP because of the limitation of quality and the number of the included studies. More large-scale, double-blind, well-designed, randomized controlled trials are needed in future research.